Immediate Implant Placement into Fresh Extraction Socket in the Mandibular Molar Sites: A Preliminary Study of a Modified Insertion Technique. (9th August 2013) - Hamouda, Nelly I.; Mourad, Samah I.; El‐Kenawy, Mohamed H.; Maria, Ola M.
Abstract: Background: Immediate implant insertion in mandibular molar extraction sockets raises a series of challenges for clinicians. Purpose: This preliminary study demonstrates the use of a modified insertion technique of implant placement at the time of mandibular molar extraction. Materials and Methods: Immediate implants were placed at the time of molar extraction in 20 patients; a sulcular buccal incision with releasing periosteal incisions were made around the mandibular molar to be replaced, and implant insertion into the interseptal/interradicular bone was performed. The remnants of roots were atraumatically extracted, and the bony defects around the implant were grafted with synthetic resorbable bone substitute β‐ Tricalcium phosphate, and the flap was sutured. Three months later, implants were restored with single crown fixed prostheses. Patients were followed up at 6, 12, and 18 months after insertion using periapical standardized radiographs to monitor the changes in the marginal bone level. Results: Our modified insertion techniques showed an implant survival rate of 95%; one implant failed 4 weeks after insertion. No significant marginal bone loss around the implant was recorded at all times of follow‐up. Satisfactory soft issue parameters were achieved. Conclusions: The combination of immediate implant placement with engagement of the interseptal/interradicular bone, atraumatic extraction of remnant roots, and concomitant regenerative therapy showed preliminary favorable outcomes. However, wider application of this technique for longer following up periods is required for further conclusive recommendations.